1999
DOI: 10.1108/eum0000000004575
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the expectations of older food consumers

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:239791 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 42 publications
3
61
1
Order By: Relevance
“…Another has looked at the shopping behaviour of older people have focused in urban and rural Scotland. Here aspects of diets, health beliefs and facilities available to older people in terms of social support differ from those in England (McKie, 1999. Hare et al, 1999.…”
Section: Figure 1 Herementioning
confidence: 99%
See 2 more Smart Citations
“…Another has looked at the shopping behaviour of older people have focused in urban and rural Scotland. Here aspects of diets, health beliefs and facilities available to older people in terms of social support differ from those in England (McKie, 1999. Hare et al, 1999.…”
Section: Figure 1 Herementioning
confidence: 99%
“…Previous research involving the shopping behaviour of older people has indicated that they may implement coping strategies in order to continue to access food in a way that enables them to manage and maintain their independence (McKie, 1999;Leighton and Seaman, 1997;Hare et al, 1999). These coping strategies include shopping more frequently or with friends or relatives, and using local shops in order to choose foods.…”
Section: Dietary Variety and Attitudes And Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Community Food and Health Scotland (2010) recognise, there are numerous potential constraints to older people accessing healthy food which, if addressed, would -by implicationbenefit others (see also Bowyer, et al, 2009). These fall into two broad categories: poverty -the costs of food, transport and personal health; and culture (or socialisation) -differential culinary skills and shopping practices (see Keane and Willetts, 1994;Herne, 1995;Donkin, et al, 1998;Hare, et al, 1999;Hughes, et al, 2004). In addressing these constraints, Morgan (2010) argues in favour of a pluralist approach to food planning in which the ecological integrity of healthy food and the social justice of its distribution are combined in a comprehensive approach to food security.…”
Section: Older People and Their (Lack Of) Food Choicementioning
confidence: 99%
“…It has also been claimed that such an approach to food distribution diminishes many older people's lives, for a range of reasons related to social and culinary alienation and stress (Hare, et al, 1999;Meneely, et al, 2009), leading to questions about distributional equity (Morgan, 2010;Morgan and Sonnino, 2010) and public health (Ellaway and Macintyre, 2000;Kyle and Blair, 2007). In addressing this situation there has been an increasing trend, in Europe and America, to question how access to fresh and healthy food can be brought into land use planning decisions (Food Commission and Sustain, n.d.;Morgan, 2009;Morgan and Sonnino, 2010).…”
Section: Introductionmentioning
confidence: 99%